Art Expression therapy helps people manage pain - Siti Nurfarmy, Ibrahim (2020)
PEKAN, 18 November 2020 - The use of spoken words to express is sometimes challenging for some individuals. Therefore, the use of art in the context of psychotherapy and counselling can help individuals in creating images and imagination in their minds creatively on drawing papers.